A Scheduling Method of Cross-Layers Optimization of Polling Weight for AOS Multiplexing - Yuntao Zhao; Bo Bo; Yongxin Feng (International Journal of Digital Multimedia Broadcasting)
The core mechanism of Advanced Orbit System (AOS) mainly contains the packet channel multiplexing and the virtual channel multiplexing. The multiplexing efficiency and frame time directly affect the performance of the AOS and even the whole system. In this paper, in order to optimize AOS multiplexing performance, a scheduling method of cross-layers optimization of polling weight (CLOPW) is proposed. Different from single sublayer optimization such as the isochronous frame methods, the novel method focuses on factors related to AOS performance of two core sublayers, such as packet distribution, residual function, cache capacity, frame time, and multiplexing efficiency. We build a multiple factors framing model of finite buffer and deduce the formula of packet multiplexing efficiency based on the short correlation. Furthermore, we give the formula for the virtual channel utilization and delay of cross-layer optimization. The experimental results show that the novel scheduling method of cross-layers optimization of polling weight is higher utilization of virtual channel and lower average delay than the isochronous frame method.